Inovasi Teknologi Sosial dalam Program LAWANG CEMORO untuk Mendukung Circular economy Masyarakat Pesisir (Lembaga Pengembangan Kinerja Dosen, 2026)
Coastal communities commonly experience interconnected environmental, social, and economic challenges, including plastic waste accumulation, limited access to clean water, and low community productivity. Addressing these issues requires an integrated approach that combines social innovation with appropriate technology. This article aims to analyze the implementation of social technology innovations in the LAWANG CEMORO (Pintu Harapan Masyarakat Semarang Utara) Program to support a community-based circular economy in Tanjung Mas Village, Semarang. The program adopted a participatory community empowerment approach involving problem identification, collaborative planning, technology implementation, capacity building, mentoring, and continuous evaluation. Four integrated innovations were implemented: POJA-PETA for plastic waste drying, Petasol for converting plastic waste into alternative fuel through pyrolysis, SITIRTA as a solar-powered environmentally friendly water filtration system, and a Greenhouse for food production and community economic empowerment. The program reduced plastic waste, improved water and energy efficiency, strengthened food security, and increased community income while enhancing local institutional capacity. This study proposes the LAWANG CEMORO Integrated Social Technology Model, which links waste management, renewable energy, water resource management, and food production within a circular economy framework. The model provides a practical reference for developing sustainable community empowerment programs in coastal areas facing similar environmental and socioeconomic challenges.